A Latent Look at Empirical Generalizations - Morrison, Donald G.; Silva-Risso, Jorge (Marketing science (Providence, R.I.), 1995)
All empirical data and the resulting parameters are subject to error. In this paper we explicitly use the standard, but hardly profound, "model" $$\hbox{Observed Value} = \hbox{True Score} + \hbox{Error}$$ as a lens for better viewing empirical studies in search of empirical generalizations in marketing. This lens is especially valuable when the unit of analysis is the individual consumer. However, even when a macro study contrasts price elasticities across cities, this O = T + E framework can be very helpful.